Review of classification schemes of moss vegetation of Western and Central Europe (CHORNOMORSKI BOTANICAL JOURNAL, 2013)
The state of study is characterized and the review of modern classification systems of moss vegetation of Western and Central Europe are given. The comparative characterization of the main classification schemes by R. Marshtaller (2006) and A. Hübschman (1986) is proposed. The correlation of higher syntaxonomical categories: classes, orders of both classification schemes is defined. The state of classification of moss vegetation in Eastern European countries and surrounding areas is given. The classification of moss vegetation of Forest-Steppe of Ukraine is proposed. It consists of 9 classes, 13 orders, 18 alliances, 36 associations, 8 subassociations, 22 moss communities and 11 epigeic synusiae. 3 associations, 4 subassociation and 14 moss communities are described as new to science.
Keywords: bryocommunities, syntacson, class, order, union, association.